AN INVESTIGATION OF THE REGULATION IN TWO GENETIC REGIONS HARBOURING ANTISENSE RNA IN STREPTOMYCES COELICOLOR - Hindra, - (My University, 2012)
Bacterial small RNAs have emerged as a class of molecules having important regulatory roles. Accumulating numbers of cis-encoded sRNAs (antisense RNAs) have been recently discovered to be transcribed from the chromosomal DNA of many bacterial species, including the streptomycetes. Here, we investigate potential regulatory roles for two S. coelicolor antisense RNAs, scr4677 and α-abeA.
The scr4677 antisense RNA is transcribed from the intergenic region between SCO4676 (a gene encoding a conserved protein of unknown function) and SCO4677, encoding a regulatory protein with proposed anti-sigma factor activity. Transcription profiling revealed that scr4677 may not only interact with SCO4676 mRNA but also with SCO4677-4676 read-through transcripts. Our study suggested that scr4677 functioned to destabilize SCO4676 mRNA, at the same time that it stabilized the SCO4677-4676 read-through transcript. The potential role for scr4677 in destabilizing SCO4676 mRNA was not mediated by the double stranded ribonuclease RNase III. Genetic analysis showed scr4677 transcription was affected by SCO4677, and the transcription was apparently dependent on an unknown protein binding to the SCO4676 coding sequence.
A second independent study focused on investigating the regulation of a previously uncharacterized genetic region, SCO3287-3290, since renamed abeABCD. This region contains an antisense RNA (α-abeA)-encoding gene, and is adjacent to the downstream SCO3291 (abeR) gene, which encodes a putative regulatory protein. Genetic analysis revealed that overexpression of abeR or abeABCD stimulated the production of the blue-pigmented antibiotic actinorhodin, and deletion of abeR impaired actinorhodin production. Transcription analysis revealed the abe genes (including α-abeA) to be subject to multiple levels of regulation. We found an internal promoter within the abeA coding sequence and that required AbeR for expression. Furthermore, biochemical experiments demonstrated that AbeR regulated abeBCD directly, by binding to four heptameric repeats in its promoter region. The expression of α-abeA and other abe genes were differentially affected by RNase III.
Keywords: regulatory rna; non coding rna; secondary metabolism; gene regulation; polycistronic; differential expression; Microbiology; Microbiology